Teknik Pengelolaan Lingkungan Hidup Di Indonesia - Dian Mahdiansah (Celebes Engineering Journal, 2019)
The phenomenon that is very urgent in Indonesia is the pollution of nature and a pile of garbage that is very important in big cities and the community does not realize that the material is circulating or cycles in the ecosystem so that it must be given enough time to be changed back from one form to the next in while undergoing the cycle. They do not provide an opportunity for spoilage microbes to carry out their functions in the material cycle process. therefore it takes stages as solution. In this study so that environmental management techniques can be realized in real life for the achievement of a healthy life.